Asymptotic solution of a harmonic contact problem for a permeable stamp on a liquid saturated base - Gomilko, A.M.; Savitsky, O.A.; Trofimchuk, A.N. (Нелінійні коливання, 2002)
A plane harmonic problem of vertical vibrations of a rigid permeable stamp on a liquid saturated poroelastic base is considered. The equations of two-phase Biot media, taking into account inertial and viscous interactions of phases, are used. The asymptotic properties of the contact stress in dependence on small frequency of vibration are studied.